Compact Cities Are Complex, Intense and Diverse but: Can We Design Such Emergent Urban Properties? - Lim, Hye Kyung (2016)
Compact cities are promoted by global and local policies in response to environmental, economic and social challenges. It is argued that increased density and diversity of urban functions and demographics are expected to deliver positive outcomes. ‘Emerged’ urban area which have developed incrementally seem to exhibit such dense and diverse characteristics, acquired through adaptation by multiple actors over time and space. Today, ‘design-based’ planning approaches aim to create the same characteristics here and now. An example of such is the City of Gothenburg, Sweden, which strives to involve multiple actors to ‘design’ urban density and mixed use, but with unsatisfactory outcomes. There is reason to investigate in what way current planning approaches need modification to better translate policy goals into reality. This paper studied which type of planning approach appears to best deliver the desired urban characteristics. Two cities are studied, Gothenburg and Tokyo. Today, these cities operate under different main planning paradigms. Tokyo applies a rule-based approach and Gothenburg a design-based approach. Five urban areas were studied in each city, representing outcomes of three strategic planning approaches that have been applied historically in both cities: 1) emergent compact urban form; 2) designed dispersed urban form; and 3) designed compact urban form. Planning outcomes in the form of density, building scales and diversity were analysed to understand if such properties of density and diversity are best achieved by a specific planning approach. The results show that different planning approaches deliver very different outcomes when it comes to these qualities. To better support ambitions for compact cities in Gothenburg, the prevailing mix of ‘planning by design’ and ‘planning by developmental control’ needs to be complemented by a third planning strategy of ‘planning by coding’ or ‘rule-based planning’. This is critical to capacitate urban planning to accommodate parameters, such as timing, density, building scale diversity, and decentralization of planning and design activities to multiple actors.